1973
DOI: 10.1039/p19730001432
|View full text |Cite
|
Sign up to set email alerts
|

Isoindole

Abstract: 2-( p-phenylethy1)isoindoline 2-oxide (VI) at 105" and 0.02 mmHg gives 2-hydroxyisoindoline (VII). The latter was contaminated with 2-( p-phenylethy1)iso-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Similarly, benzo proton signals for 2BN (d = 7.37 and 7.20 ppm) appeared at higher field than for 2BS (d = 8.05 and 7.59 ppm), whereas the bproton signals in the spectrum of 2BN (d = 9.34 ppm) were observed at lower field than in the case of 2BS (8.33 ppm). As benzo protons of the parent heterocycles exhibit similar chemical shifts (d = 7.5 and 6.8 for isoindole and d = 7.59 and 7.04 for isothianaphthene), [23] these observed differences can be attributed to differences in the diamagnetic macrocyclic ring currents ( Figure 1).…”
Section: Nmr Spectroscopymentioning
confidence: 86%
“…Similarly, benzo proton signals for 2BN (d = 7.37 and 7.20 ppm) appeared at higher field than for 2BS (d = 8.05 and 7.59 ppm), whereas the bproton signals in the spectrum of 2BN (d = 9.34 ppm) were observed at lower field than in the case of 2BS (8.33 ppm). As benzo protons of the parent heterocycles exhibit similar chemical shifts (d = 7.5 and 6.8 for isoindole and d = 7.59 and 7.04 for isothianaphthene), [23] these observed differences can be attributed to differences in the diamagnetic macrocyclic ring currents ( Figure 1).…”
Section: Nmr Spectroscopymentioning
confidence: 86%
“…Under appropriate conditions the coupled oxidation of hernochromes is rapid and leads t o a good yield of bile pigment. 78 On the other hand, with heme proteins the reaction is slow and in general biliverdin is obtained in very small yield.7 3 , 7 5 High concentrations of oxygen accelerate the coupled oxidation of pyridine h e r n o c h r~m e~~ yet, paradoxically, inhibit the coupled oxidation of h e m~g l o b i n .~~ Most importantly, the two processes show a marked difference in stereospecificity, as described below.…”
mentioning
confidence: 99%
“…An overall yield of 11.1% of the mixture of hematobiliverdin methyl esters was obtained. This yield, although lower than that obtained for the oxidation of hemin IX to the biliverdin IX isomers (42% [9]) is not very different from the yields of the biliverdin methyl esters obtained in the oxidation ofuroheme I11 (8.3% [lo]) or coproheme 111 (12.1%…”
Section: Chemical Oxidation Of Hematohemin To Hematobiliverdinsmentioning
confidence: 95%
“…As a first step in these studies we performed the chemical oxidation ('coupled oxidation' [9]) of synthetic hematohemin IX to the four possible hematobiliverdin isomers (a, p, y and 6). We found that, contrary to the negative previous report [8], the reaction took place in low but similar yield to that reported in the chemical oxidations of other hemins.…”
mentioning
confidence: 99%